La déformation : Bataille et l'irreprésentable - Apicella, Nicola (Labyrinth, 2020)
The deformation: Bataille and the irrepresentable The present article is focused on the interactions of matter and form in the writings of Georges Bataille. Starting with the notion of "formless" (informe) that he outlined in the journal Documents (1929) and through Georges Didi-Huberman's text on the "formless resemblance" (1995), we will try to show how, in Bataille's work, high and low respond to each other and intertwine to generate a "spastic" device of deformation that allows the desire to reshape the writing and the images that surround it. For this purpose, we will apply Gilles Deleuze's approach to the painting of Francis Bacon, which is fundamentally opposed to "representation" in order to achieve what Deleuze calls the "pure figurative" (expression of sensations, affects and impulses). The approach will help us to understand how Bataille's works respond to the same demand for "material deformation" and "formal materialization", which manifests itself by accident and is addressed less to the understanding than to sensibility.